Assessing the impact of peacebuilding on human security in conflict-affected states: the case of Côte d’Ivoire (2002-2015) - Ateku, Abdul-Jalilu (2018)
This thesis examines the impact of peacebuilding on human security in Côte d’Ivoire (2002- 2015). It makes both a theoretical and empirical contribution to the literature on peacebuilding and human security. Theoretically, the study offers a framework to assess the impact of peacebuilding initiatives. It is based on literature on human security and peace and the interviews I conducted with 62 research participants. They were officials of international governmental and international non-governmental organisations, Ivorian national security institutions, peace and security experts, officials of local NGOs, citizens, and community leaders. I identify four areas of assessment for the impact on human security: personal safety of people, human rights, health and education. All the four areas are hinged on the three key elements of human security - “freedom from fear”, “freedom from want” and “freedom from indignity.” The four main variables used in assessing the impact of peacebuilding addressed issues relating to all the seven except one of the human security indicators espoused in the 1994 United Nations Development Programme Human Security report. The only exception is the environmental indicator which has been partly discussed in the health area. Environment could not be fully analysed for security reasons at the time of data collection in the most environmentally affected areas in the West of Côte d’Ivoire. Empirically, the study uses this framework to analyse the impact of peacebuilding on human security in Côte d’Ivoire. International peacebuilding by the United Nations (UN), African Union (AU), European Union (EU), Economic Community of West African States (ECOWAS), and France prioritised issues of elections, re-establishing of democracy, and disarmament and demobilisation of combatants, and the development of state security over health and education. The study argues that: 1) the latter are more important than the former for durable peace in conflict-affected states; and 2) peacebuilders have an overall limited positive impact –and in some cases made no impact on human security. Peacebuilders’ interventions failed to protect people’s personal safety. They could not retrieve most of the arms, and only reintegrated a few former fighters into their economically impoverished communities. The limited number of peacekeepers, and their geographically-limited areas of deployment affected their protection responsibility of citizens’ personal safety. About 6200 peacekeepers were deployed in 2004 which was increased to 8000 in 2008. The peacekeepers’ peak strength of 9700 in 2012 was reduced to 4000 by December, 2015. Their geographically-limited areas of deployment exposed citizens to various forms of abuses and killings. By the end of 2015, citizens continue to experience violent crime resulting from the war, but on a reduced scale. Peacebuilders’ policies to address gross violations of human rights made only a minimal impact. Only President Laurent Gbagbo, his wife, Simone Gbagbo, and the youth leader from pro-Gbagbo camp, Charles Blé Goudé have been indicted by the International Criminal Court (ICC) for war crimes, with President Gbagbo and Blé Goudé alone currently standing trial at the ICC. Individuals and groups from the pro-Ouattara camp who perpetrated sexual abuses, torture and extra-judicial killings have not been held liable for the egregious violations of human rights by either a domestic court or the ICC. Sexual abuse remains an issue to be comprehensively addressed by local and international institutions. United Nations agencies, notably United Nations Children’s Fund, United Nations Educational, Scientific and Cultural Organisation, World Health Organisation and others such as the French government’s Agence Française de Développement have been the main actors in the implementation of education and health policies in war-affected communities. They built schools, provided teaching and learning materials, recruited teachers and implemented policies intended to address problems that affected children’s enrolment, drop-out rates, female children’s retention in school, completion rates and pupil-teacher ratio. Nonetheless, their policies have had extremely limited impact on gender-based violence, inequality and discrimination perpetrated against girls in school. Others included lack of classrooms and facilities such as toilets, lack of teachers, no or poor counselling services, high poverty and inequality. Peacebuilding interventions have also not obliterated war-related health effects. Access to preventive and treatable healthcare services to address infant and maternal health problems remains extremely low among war affected populations in Côte d’Ivoire. Children face a high risk of dying due to low access to paediatric services such as immunisations, extremely low access to antenatal and postnatal services by women owing to poorly equipped medical facilities and inadequacy of professional birth attendants is a debilitating factor to the health of pregnant women. This has resulted in poor maternal health outcomes. The war-affected populations are still exposed to other health-risks. They lack safe water and face food shortage. They are exposed to poor hygienic practices. They still have to deal with poor sanitation, and poor shelter. The thesis concludes with recommendations to mainstream critical health and education issues which are essential in human security in peacebuilding in order to make peacebuilding more successful in the long term in war-affected states.